An unusual complication of pyloric ring obstruction caused by flange of lumen apposing metal stent in endoscopic ultrasound-guided gallbladder drainage: A case report. Issue 27 (2nd July 2020) - Seo, Seung Young; Lee, Chang Hun; Kim, In Hee; Kim, Sang Wook; Lee, Seung Ok; Lee, Soo Teik; Kim, Seong-Hun
Abstract: Introduction: Endoscopic ultrasound-guided gallbladder drainage (EUS-GBD) is an alternative treatment option for patients with acute cholecystitis, especially for those who are unsuitable for cholecystectomy. Recently used luminal apposing metal stents (LAMS) in EUS-GBD has several advantages over standard metal stents. However, there is no current guideline on where to locate the LAMS when transgastric approach is required. This study reports a case of gastric outlet obstruction (GOO) by placing LAMS too close to the pyloric ring. Patient concerns: A 79-year-old female patient was referred to our department for evaluation of a large hepatic mass on abdominal ultrasound. Abdominal pain on right upper quadrant and spiking fever up to 38 °C appeared after liver biopsy. Abdominal ultrasound showed thickened GB wall and positive sonographic Murphy sign. Diagnoses: Intrahepatic cholangiocarcinoma with multiple lung and intrahepatic metastasis, acute cholecystitis, and pyloric ring obstruction caused by flange of LAMS in EUS-GBD. Interventions: EUS-GBD via transgastric approach was performed with LAMS. After complete deployment of stent, esophagogastroduodenoscopy showed complete GOO by flange of LAMS. A gastroduodenal metal stent was inserted to relieve the GOO. Outcomes: The patient recovered well. She did not complain about obstruction induced symptom such as vomiting or abdominal fullness after gastroduodenal stent insertion. Conclusion: To the best of our knowledge, this is the first case report of EUS-GBD induced GOO. If physicians use LAMS as a transgastric approach in EUS-GBD, the puncture site should be carefully selected considering the size of the flange.